Ekstensifikasi Dan Kepatuhan Wajib Pajak Menyampaikan Surat Pemberitahuan Terhadap Penerimaan PPh Pasal 21 - Edi Tri Wibowo, Dian. S. Wulandari, (Jurnal Ekonomi, 2019)
This study aims to determine whether there is an effect of tax extensification and level of compliance partially or simultaneously to the level of income tax revenue. This study uses secondary data obtained from the Primary Tax Office (KPP) Cibitung and the Central Statistics Agency (BPS) of Bekasi Regency. The data analysis method used is the classical assumption test and hypothesis testing. The statistical method used is linear linear regression analysis. The results show that partially tax extensification and the level of taxpayer compliance do not affect the level of income tax revenue. The results of simultaneous tax extensification and the level of taxpayer compliance do not affect the level of income tax revenue. Tax extensification and the level of compliance affect the level of income tax revenue by 25,7 %. While the remaining 74,3 % is influenced by other variables that are not explained in the regression model.